RULES ASSOCIATION FP-GROWTH DALAM ANALISIS KERANJANG PASAR - Butar Butar, Masro Shausi; Elisa, Erlin (LPPM Universitas Putera Batam, 2022)
Nowadays, the cosmetic industry is constantly developing as the economic keep ascending. In this industry, innovation for skincare or bodycare treatment attracts more consumers. Kiki Ms Glow is one of the retails that selling cosmetics and bodycares. In transaction, they uses cash and manual reports. Because of that, analyzing consumers cross selling is needed to know consumer buy patterns and sales growth. A way to know conditions for observing sales transaction data by using data mining. The method that used to analyze market basket is the association rule. The association rule able to give product recommendations, so that the marketing strategy is more focused and the products promoted are the customer's wants. At Kiki Ms Glow, the deduction of product recomendations are acquired from analyzing of sales transaction data reports. The motive of this study is get to know consumer’s buying pattern using algorithm FP-Growth in producing product recommendation rules on a large number of datasets so that they can provide technical recommendations. The results obtained are from the highest by a minimum support value of 20% and a minimum value of 70% confidence, and the result is found 2 rules